Efficient direct shoot organogenesis and genetic stability in micropropagated sacha inchi (Plukenetia volubilis L.) (2020)
Objective: It is necessary to improve biotech platforms based on in vitro cell tissue culture to support sacha inchi (Plukenetia volubilis L.) research programs and draw on the nutritional value of the high polyunsaturated fatty acid content of its oilseed. Here, we developed a rapid and efficient method for induction and direct in vitro shoot development for this species. Results: Shoots were generated from hypocotyl explants. The highest organogenic response was obtained in woody plant medium supplemented with 1 mg/L thidiazuron and 0.5 mg/L zeatin supplemented with L-glutamine, adenine hemisulfate, and L-arginine. Shoots obtained using this medium were transferred and subcultivated with different concentrations of indole-3-butyric acid and 1-naphthylacetic acid for rooting. For the first time, a histological analysis was performed supporting direct organogenic development in this species. The plantlets obtained were transferred ex vitro with a survival percentage of 80%. The genetic stability of the plants recovered was confirmed by randomly amplified polymorphic DNA analysis. All results indicate that it would be possible to stimulate direct shoot formation from hypocotyls to support the sustainable use of this species. © 2020 The Author(s).